FUNCTIONAL PROPERTIES OF PVDF-BASED NZF-BT FLEXIBLE FILMS - Grigalaitis, R.; Salasevicius, R.; Banys, J.; Petrovic, M. Vijatovic; Dzunuzovic, A.; Zaghete, M. A. [UNESP]; Teixeira, G. F. [UNESP]; Stojanovic, B. (Lithuanian Physical Soc, 2022)
Flexible multiferroic composite films are perspective materials for sensors, actuators and similar components of wearable and stretchable devices. Here we present the study of functional properties of flexible composites prepared by embedding nickel zinc ferrite and barium titanate powder into polyvinylidene fluoride (PVDF) polymer optimizing the ratio of polymer and fillers to get the best flexibility and functionality. ATR-FTIR analysis revealed that hot pressing of the flexible films caused a transformation of about 38% of the electro-inactive PVDF alpha phase into electrically active beta and gamma phases. Broadband dielectric spectroscopy revealed two relaxation processes responsible for PVDF and space charge relaxations. Activation energies of both processes and the freezing temperature of PVDF to the glass phase were estimated for all films. Ferroelectric measurements have shown unsaturated hysteresis loops for all samples, although the clear dependence of the amount of the electrically active phase on polarization values of composites is visible.
Keywords: composites; flexible films; ferroelectric properties; dielectric dispersion